UPLC/Q-TOF-MS/MS-based metabolomics revealed the lipid-lowering effect of Ilicis Rotundae Cortex on high-fat diet induced hyperlipidemia rats. (28th June 2020) - Yang, Bao; Xuan, Shenxin; Ruan, Qingfeng; Jiang, Shiqin; Cui, Hui; Zhu, Liping; Luo, Xiang; Jin, Jing; Zhao, Zhongxiang
Abstract: Ethnopharmacological relevance: Ilicis Rotundae Cortex (IRC), a Chinese crude drug, has been widely utilized in Guangdong and Guangxi provinces of China to treat or prevent cardiovascular diseases. Aim of study: This investigation aims to study the lipid-lowering effect of IRC, as well as the regulating effect on the endogenous metabolites in hyperlipidemia rats. Materials and methods: High-fat diet induced hyperlipidemia rats were administrated with different doses of IRC extract (0.5, 1.0 and 2.0 g/kg/day) for 5 weeks. Simvastatin was used as the positive control. Body weight, serum lipid levels and histopathology of liver were evaluated. The metabolic profiles of plasma, urine and cecum content were analyzed using UPLC/Q-TOF-MS/MS-based metabolomics approach coupled with multivariate data analysis. Results: The levels of serum TC, TG, LDL-C, AST and ALT were significantly decreased and HDL-C level was increased in IRC treatment groups. The hepatic histomorphology was partially restored. 23, 26 and 15 metabolites in plasma, urine and cecum content were determined as the biological biomarkers, respectively. IRC extract could partially recover the disturbed metabolic pathways of bile acid metabolism, linoleic acid metabolism, arachidonic acid metabolism, taurine and hypotaurine metabolism, glyoxylate and dicarboxylate metabolism, glycerophospholipid metabolism, synthesis and degradation of ketone bodies, sphingolipid metabolism and riboflavin metabolism. Conclusion: This study demonstrated that IRC could effectively improve the serum lipids and partially restore the hepatic histomorphology. The underlying metabolic mechanism mainly included improving the metabolism of bile acids, glycerophospholipid, sphingolipid, fatty acid and amino acid. This is the first study on the lipid-lowering effect of IRC from the perspective of metabolomics. Graphical abstract: Image 1